Comprehensive morphological and biochemical characterization of garlic (Allium sativum L.) genotypes using multivariate analysis - İbrahim Sönmez; Ümit Haydar Erol; Kamil Sarpkaya (BMC Plant Biology)
Abstract Background Garlic (Allium sativum L.) is an economically and nutritionally important plant species with high genetic diversity bearing rich biochemical compounds. The aim of this study is to evaluate and compare the morphological composition and chemical properties of 17 genotypes of garlic consisting of 15 genotypes collected from various regions of Türkiye and two superior genotypes from China and Iran. The examined genotypes in this research are: "Isparta-Çaltı", " Aksaray-Local", "Tokat-Local1", "Çorum-Üyük","Iran", "Kırklareli-Vize", "Tokat-Local2","Antalya-Kemer", "Antalya-Elmalı","Kastamonu-Taşköprü", "Balıkesir-Cinge","Konya-Akşehir", "Aksaray-Purple","Şanlıurfa-Birecik", "Kütahya-Germiyan","Aksaray-White", "China". This research targeted superior genotypes by analyzing morphological traits, mineral content, organic acid profiles, and sugar compositions. Results The genotypes examined in this study exhibited significant differences in morphological traits, elemental composition, organic acids, and sugars (p<0.05). Plant height ranged from 85.6 cm (G3) to 102.0 cm (G1), and leaf number from 8.0 (G17) to 13.4 (G10, G12). Sucrose levels in cloves varied from 2,461.15 mg/kg (G12) to 13,727.28 mg/kg (G16), while potassium content ranged from 807.7 mg/kg (G17) to 1,695.7 mg/kg (G9). PCA revealed that PC1 (29.37%) represented elements and organic acids, PC2 (14.70%) reflected sugars, and PC3 (10.47%) was associated with morphological traits related to N and P accumulation. Correlation analysis showed positive associations such as leaf width with pseudostem width (r=0.64) and potassium with magnesium (r=0.82), suggesting coordinated nutrient uptake. Negative correlations were found between sodium and nitrogen (r=–0.21), and malic acid and glucose (r=–0.52), indicating potential metabolic trade-offs. G14 appeared unique morphologically and biochemically, while G10, G11, and G12 clustered due to similar profiles. These findings highlight the potential of garlic genotypes for functional evaluation and breeding program development. Conclusions This analysis determined that remarkable differences existed among the genotypes in terms of morphological characteristics, mineral composition, sugars, and organic acid profiles, which informed important breeding and functional product development. Genotypes G10, G12, and G14 exhibited superior morphological features with rich mineral content, while high levels of bioactive compounds (micronutrients and organic acids) in G6, G8, and G16 distinguished them biochemically. The use of multivariate statistical analysis allowed accurate differentiation among genotypes based on their structure and biochemical properties, paving the way for specific breeding strategies. The results are of great importance as a reference in the selection of genotypes with high nutritional quality and industrial utility.